DAMPAK AUDIT OPERASIONAL FUNGSI PRODUKSI TERHADAP PRODUKTIVITAS PADA PT.MEGAFLEX PRATAMA - Wahyuni, Giati; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the influence of the production function of operational audit to theproductivity on PT Megaflex Pratama, Sidoarjo. This research is qualitative descriptive research method whichhas been carried out to find out the influence of the production function of operational audit to the productivity.The data collection technique has been carried out by using preliminary survey, field research and literatureassessment. Preliminary surveys in which the researcher conducts the survey on the company which will beselected as the research object and ask permission to the manager of the company to conduct the research. Thefield survey is conducted to collect the data which is required by performing observation, interview, anddocumentation. The literature assessment has been conducted in order to obtain secondary data which will beuseful as the theoretical guideline in conducting the field research. The result of the research shows that there is avalidation between the result of operational audit statement which has been prepared by the internal auditor withthe real condition in the company. Therefore, it can be concluded that the impact of production function ofoperational audit to the productivity is positive impact. It can be seen from the comparison between the salesdata (unit) and the turnover data (Rp) from 2012 to 2013.Keywords: Operational Audit, Production Function, and Productivity.